New roles of deacetylase inhibitors in the modulation of mitochondrial amino acid oxidation and nitrogen metabolism - Moedas, Marco Filipe Semião, 1986- (2017)
Tese de doutoramento, Farmácia (Bioquímica), Universidade de Lisboa, Faculdade de Farmácia, 2017